Predicting Bystander Intention to Intervene: The Role of Gender-Specific System Justification and Rape Myth Acceptance for Men and Women - Martini, Mara; De Piccoli, Norma (Frontiers in Psychology, 2020)
The relationship between rape myth acceptance, gender-specific system justification (GSJ), and bystander intention to intervene has often been studied on a one-dimensional basis, without separating the four dimensions of the acceptance of rape myths. The current study analyzes the relationship between the acceptance of rape myths, GSJ, and bystander intention to intervene, and explores whether the relationships operate differently for men and women. The sample was 3,966 university students: 2,962 from the University of Turin and 1,004 from the Politecnico of Turin; 71.2% women and 28.8% men; average age of 22.61 years. After descriptive analyses, independent sample T-test, and bivariate correlations, a model where the acceptance of four rape myths (“She asked for it”; “He didn’t mean to”; “It wasn’t really rape”; “She lied”) mediated the relationship between GSJ and bystander intention to intervene was tested on the whole sample and then separately on women and men. A bootstrapping procedure was applied. Our data show that for both men and women, GSJ was related to the four rape myths, whereas women and men differed on the relationship between acceptance of rape myths and bystander intention to intervene: only the dimension “She asked for it” was significant for both groups; the dimension “It wasn’t really rape” was significant only for the men. Focusing on the differences in women and men regarding acceptance of rape myths can be fruitful for a theoretical deepening of the field and may inform the development of more successful prevention programs.